INVESTIGATING THE ROLE OF KLOTHO IN DIABETIC NEPHROPATHY: CORRELATION WITH GLYCEMIC STATUS - Botirova Nigina Akram qizi (Scholar Express Journals, 2024)
Diabetic nephropathy (DN) is a prevalent and severe complication of diabetes mellitus that leads to progressive kidney damage, often culminating in endstage renal disease (ESRD). The pathogenesis of DN is multifactorial, involving chronic hyperglycemia, oxidative stress, inflammation, and fibrosis. Despite advances in therapeutic strategies, DN remains a significant cause of morbidity and mortality in diabetic patients. Therefore, identifying novel biomarkers and therapeutic targets is crucial to improve the management of DN. One such promising target is Klotho, a protein that has garnered attention due to its potential anti-aging, anti-inflammatory, and renal protective properties.
Keywords: Cystatin C; glycated hemoglobin; diabetic nephropathy; glomerular filtration rate